A Cattle–Human Comparative Map Built with Cattle BAC-Ends and Human Genome Sequence - Larkin, Denis M.; Everts-van der Wind, Annelie; Rebeiz, Mark; Schweitzer, Peter A.; Bachman, Sharon; Green, Cheryl; Wright, Chris L.; Campos, Edhilvia J.; Benson, Leslie D.; Edwards, Jennifer; Liu, Lei; Osoegawa, Kazutoyo; et al. (Genome Research, 2003)
As a step toward the goal of adding the cattle genome to those available for multispecies comparative genome analysis, 40,224 cattle BAC clones were end-sequenced, yielding 60,547 sequences (BAC end sequences, BESs) after trimming with an average read length of 515 bp. Cattle BACs were anchored to the human and mouse genome sequences by BLASTN search, revealing 29.4% and 10.1% significant hits (E < e-5), respectively. More than 60% of all cattle BES hits in both the human and mouse genomes are located within known genes. In order to confirm in silico predictions of orthology and their relative position on cattle chromosomes, 84 cattle BESs with similarity to sequences on HSA11 were mapped using a cattle–hamster radiation hybrid (RH) panel. Resulting RH maps of BTA15 and BTA29 cover ∼85% of HSA11 sequence, revealing a complex patchwork shuffling of segments not explained by a simple translocation followed by internal rearrangements. Overlay of the mouse conserved syntenies onto HSA11 revealed that segmental boundaries appear to be conserved in all three species. The BAC clone-based comparative map provides a foundation for the evolutionary analysis of mammalian karyotypes and for sequencing of the cattle genome.